Shenyun before Wang Shizhen: A Terminological Study of Hu Yinglin's and Lu Shiyong's Poetics. (2nd January 2016) - Wong, Chi-hung
Abstract : Shenyun (神韻 spirit resonance) is a concept that has consistently attracted scholarly attention in the field of Chinese literary criticism. Originally a principle in Chinese painting appreciation, shenyun appealed to literary critics and became a major criterion of literary composition after its widespread use in the work of Wang Shizhen (王士禛, 1634–1711) during the Qing dynasty (1636–1912). However, scholars view the Yuan (1271–1368) critics' application of the concept in poetry analysis as the earliest evidence of its use. Nevertheless, like most Chinese poetic keywords, the meaning of shenyun varies depending on both context and usage. To explore the early features of this common term, this paper examines shenyun as used in Hu Yinglin's (胡應麟, 1551–1602) Shisou (詩藪 Thicket of Remarks on Poetry ) and Lu Shiyong's (陸時雍, fl. 1633) writings. A close reading of both of these writers reveals that when shenyun is applied in contradictory ways in Shisou (which occurred before Wang Shizhen's promotion of the term), it can essentially be understood as "vitality." Wang's theoretical foundation shows that Wang's and Hu's perspectives clearly differ based on Xue Hui's (薛蕙, 1489–1539) commentaries. In this paper, I will offer a clear explanation of shenyun by examining previous scholars' explanations of the term.